2012
DOI: 10.3897/zookeys.165.2206
|View full text |Cite
|
Sign up to set email alerts
|

Cuban Calisto (Lepidoptera, Nymphalidae, Satyrinae), a review based on morphological and DNA data

Abstract: The Cuban species of Calisto are reviewed based on the morphology of adult and immature stages, as well as DNA sequences of six genes (COI, EF1α, wingless, GAPDH, RpS5, CAD). A new species, Calisto occulta sp. n., is described from the northeastern Cuban mountains. Calisto smintheus Bates, 1935 and Calisto bruneri, Michener 1949 are revised and revalidated. A new status, the species level, is proposed for Calisto brochei, Torre 1973, Calisto muripetens, Bates 1939 and Calisto bradleyi, Munroe 1950. The immatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Such structures have been used in several taxonomic studies on satyrine butterflies to species delimitation, based on its presence, shape, colour and position (i.e. Zubek & Pyrcz 2011;Aguila et al 2012;Freitas et al 2013), and play a role on sexual selection by dissemination of pheromones to influence female behaviour (Hall & Harvey 2002). However, futures studies might be focused on ultrastructure comparative morphology of the scales from androconial patch, and chemical composition analysis of pheromones to evaluate the characters are among "Pierella lamia species group".…”
Section: Discussionmentioning
confidence: 99%
“…Such structures have been used in several taxonomic studies on satyrine butterflies to species delimitation, based on its presence, shape, colour and position (i.e. Zubek & Pyrcz 2011;Aguila et al 2012;Freitas et al 2013), and play a role on sexual selection by dissemination of pheromones to influence female behaviour (Hall & Harvey 2002). However, futures studies might be focused on ultrastructure comparative morphology of the scales from androconial patch, and chemical composition analysis of pheromones to evaluate the characters are among "Pierella lamia species group".…”
Section: Discussionmentioning
confidence: 99%
“…The genus Calisto comprises 44 described species, all geographically restricted to single islands [23,26-29]; 11 distributed in Cuba, 1 in Puerto Rico, 1 in Anegada Island, 1 in Jamaica, 2 in the Bahamas and the remaining 28 species occurring in Hispaniola. Molecular data has given insight into the cryptic condition of several taxa in Hispaniola [27], as well as assisted in determining the phylogenetic relationships of Cuban taxa [28]. …”
Section: Introductionmentioning
confidence: 99%
“…Once Calisto colonized the Greater Antilles, further differentiation by vicariance [31,37], within-island diversification [28,36] or adaptive radiation [27] might have shaped the evolution of these butterflies.…”
Section: Introductionmentioning
confidence: 99%
“…Third, as for many other butterflies groups, the advent of DNA studies has revealed the existence of hidden cryptic species within Calisto. These species once discovered and thoroughly studied showed small but constant morphological differences as evidenced in Cuban species (Núñez et al 2012(Núñez et al , 2013.…”
Section: Discussionmentioning
confidence: 98%
“…The largest portion of this diversity corresponds to Hispaniola with 28 species (Sourakov & Zakharov 2011, Matos-Maraví et al 2014. The genus has received great attention since the end of nineteen century with dozens of works published including an increasing number after the arrival of molecular studies (Sourakov & Zakharov 2011, Núñez et al 2012, 213, Matos-Maraví et al 2014).…”
Section: Introductionmentioning
confidence: 99%